Global bioethics and human rights: a possible universal foundation for Bioethics? Problems and perspectives - Borgoño Barros, Cristián (Acta Bioethica, 2009)
The article shows the current status of debate on the possibility to found a bioethics of universal reach. The article gives particular attention to the intent to invoke the paradigm of human rights, displaying the strengths and weaknesses of this option, that has appeared to have reached a certain maturity with the adoption of the Oviedo Convention and the Universal Declaration of Bioethics and Human Rights of UNESCO. It poses the necessity to reconsider a concept of human dignity which is in agreement with the original intention of the authors of the 1948 Declaration of Human Rights, in order to avoid the danger of fragmentation and ambiguity of this concept.